Score Lrinec como predictor de fascitis necrotizante en pacientes con infección de piel y tejidos blandos - González Alfaro, Irvin Jair (2016)
To determine whether the LRINEC Score is a good predictor for the diagnosis of Necrotizing fasciitis (NF) in patients with skin and soft tissue infection attended in Belen Hospital of Trujillo during the years 2002-2012. MATERIALS AND METHODS: 228 medical records of Belen Hospital of Trujillo of which 65 were diagnosed with NF and 163 other types of skin and soft tissue infection were reviewed. Tetrachoric table where one in which the sensitivity, specificity, positive and negative predictive values (PPV and NPV) were calculated. By calculating the square Xi- association between the two variables of the study and the significance of it was determined; ROC curve determined the cut for this LRINEC Score. RESULTS: The most affected age group was between 51 and 60 years old, mostly male. The sensitivity and specificity of LRINEC Score in this study were 76.9% and 69.3% respectively. The PPV was 50% and the NPV was 88.28% for the Score LRINEC. The Xi-square proved to be significant (p <0.01). Likewise, the cutoff for the Score LRINEC as ROC curve was 5,5 points, with an area under the curve of 0.83 CONCLUSIONS: LRINEC Score is a good predictor of necrotizing fasciitis in patients with infection of skin and soft tissue attended in Belen Hospital of Trujillo during the years 2002-2012